2020
DOI: 10.3168/jds.2019-17407
|View full text |Cite
|
Sign up to set email alerts
|

Modeling fatty acids for dairy cattle: Models to predict total fatty acid concentration and fatty acid digestion of feedstuffs

Abstract: Development of predictive models of fatty acid (FA) use by dairy cattle still faces challenges due to high variation in FA composition among feedstuffs and fat supplements. Two meta-analytical studies were carried out to develop empirical models for estimating (1) the total FA concentration of feedstuffs, and (2) the apparent total-tract digestibility of total FA (DCFA TTa ) in dairy cows fed different fat types. In study 1, individual feedstuff data for total crude fat (EE) and FA were taken from commercial l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 62 publications
0
7
1
Order By: Relevance
“…First, studies feeding highly pure PA and SA with minimal to no unsaturated fat report large decreases in digestibility. The recent analysis by Daley et al (2020) reported that supplements containing >90% PA or SA negatively influenced FA digestibility compared with more moderately enriched supplements or blends of PA and SA. For example, Piantoni et al (2013) reported that a 99% C16:0 PA supplement decreased total and C16 FA digestibility by 10.1 and 17.4 percentage units, and Piantoni et al (2015) showed that a 98% C18:0 supplement decreased total FA digestibility by 19.5 units and C18 digestibly by 23.8 units with no effect on C16 digestibility.…”
Section: Fatty Acid Intake and Digestibilitymentioning
confidence: 99%
See 2 more Smart Citations
“…First, studies feeding highly pure PA and SA with minimal to no unsaturated fat report large decreases in digestibility. The recent analysis by Daley et al (2020) reported that supplements containing >90% PA or SA negatively influenced FA digestibility compared with more moderately enriched supplements or blends of PA and SA. For example, Piantoni et al (2013) reported that a 99% C16:0 PA supplement decreased total and C16 FA digestibility by 10.1 and 17.4 percentage units, and Piantoni et al (2015) showed that a 98% C18:0 supplement decreased total FA digestibility by 19.5 units and C18 digestibly by 23.8 units with no effect on C16 digestibility.…”
Section: Fatty Acid Intake and Digestibilitymentioning
confidence: 99%
“…Supplements predominantly containing SA have been reported to have little effect on DMI, but this has been investigated to a lesser extent and primarily in prills with very low levels of unsaturated FA (Piantoni et al, 2015;Boerman et al, 2017). Rico et al (2014b) directly compared PA and SA supplements, but utilized very high-purity supplements, which tend to have low digestibility (Daley et al, 2020). Blends of PA and SA have been most extensively investigated, and gener-ally PA combined with SA does not affect DMI (Allen, 2000) but does increase milk, milk fat, and milk protein yields (Hu et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the total production of ether extract (Table 5) and linoleic (C18: 2) and linolenic (C18: 3) fatty acids, there was a significant increase (P <0.05) due to the addition of topdressing nitrogen fertilization, but it did not influence (P >0.05) the production of oleic fatty acid (C18: 1). Recently, Tran et al (2020) and Daley, Armentano, Kononoff and Hanigan (2020) presented the results of scientific studies carried out in the United States of America, aiming to detail the fatty acid composition of the foods offered to dairy cows since the partitioning of fibrous and non-fibrous carbohydrates and nitrogen constituents are already well determined through the Cornell Net Carbohydrate and Protein System (CNCPS), and their effects on animals and the products generated (meat and milk) are understood. However, it is still essential to better understand the effects of lipids.…”
Section: Resultsmentioning
confidence: 99%
“…Previously derived coefficients for total-tract, apparent digestibility of total FA for each dietary fat source (Daley et al, 2020) were used to calculate digested intakes of total FA. For AA, the diet composition and DMI were used to calculate the intakes of each AA (Arg, His, Ile, Leu, Lys, Met, Phe, Thr, Val).…”
Section: Calculationsmentioning
confidence: 99%